2015
DOI: 10.1186/s12937-015-0108-y
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss therapy for clinical management of patients with some atherosclerotic diseases: a randomized clinical trial

Abstract: BackgroundThe prevalence and burden of atherosclerotic (AS) diseases are increasing during the last twenty years. Some studies show a close relationship between overweight and AS, but influence on AS diseases of different weight loss methods are still studying. The purpose of the research was to study the effectiveness of a weight loss program in AS patients in randomized controlled trial, and to develop a conception of evolution of AS.MethodsA randomized controlled prospective clinical trial including 97 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Since obesity is a risk factor of CVDs, the direct potential effect of CR in the prevention of CVDs is attributed to body weight reduction. Another randomized controlled clinical trial indicated that weight loss due to CR significantly improves the cardiac ejection fraction and systolic output in CAD individuals ( Oshakbayev et al, 2015 ). In 47 obese subjects undergoing 12-week CR, body weight reduction along with visceral fat area alteration was observed, which was correlated with relieved arterial stiffness measured by a decrease in cardio-ankle vascular index (CAVI) ( Nagayama et al, 2013 ).…”
Section: Interventions Targeting Sirt1mentioning
confidence: 99%
“…Since obesity is a risk factor of CVDs, the direct potential effect of CR in the prevention of CVDs is attributed to body weight reduction. Another randomized controlled clinical trial indicated that weight loss due to CR significantly improves the cardiac ejection fraction and systolic output in CAD individuals ( Oshakbayev et al, 2015 ). In 47 obese subjects undergoing 12-week CR, body weight reduction along with visceral fat area alteration was observed, which was correlated with relieved arterial stiffness measured by a decrease in cardio-ankle vascular index (CAVI) ( Nagayama et al, 2013 ).…”
Section: Interventions Targeting Sirt1mentioning
confidence: 99%
“…Endogenous lipolysis provides the body with nutrients, vitamins, trace elements. [61,62] Endogenous lipolysis starts only after ending of carbohydrate store, after 4-5 days of restriction diet. [73] Having a single meal per workday (usually after workhours) could be one of the modes to prevent weight regain.…”
Section: Resultsmentioning
confidence: 99%
“…[73] Having a single meal per workday (usually after workhours) could be one of the modes to prevent weight regain. [62,74] Conclusions (1) Body mass and food intake are the main causes to maintain high MR. Overweight is a balance between body potential energy and nutrient reserve.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity leads to an increase in the metabolic burden of the body as there is requirement for additional thermoregulation, synthetic, trophic, immunological, antitoxic functions and excretion of metabolic products from the tissue [ 7 ].…”
Section: Discussionmentioning
confidence: 99%